Composite fabric with synergistic warm-keeping and heat-insulating functions and preparation method of composite fabric

By combining the modified SiO2 electrospinning film with the modified polyurethane coating with the modified warm yarn fabric, the problems of complex structure and poor thermal insulation effect of traditional thermal insulation fabrics are solved, and the effects of simple structure, strong thermal insulation performance, breathable and moisture-permeable, and comfortable to wear are achieved.

CN119872029APending Publication Date: 2025-04-25GUANGZHOU CAMEL HOME TEXTILE TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510011569.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-04
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Traditional thermal insulation fabrics have complex structures, which affect the comfort of wearing and have problems with poor thermal insulation effect.

Method used

By combining the modified SiO2 electrospinning film with the modified polyurethane coating with the modified warm-insulating yarn fabric, a composite fabric that is synergistically insulated is formed. The fabric improves the bonding fastness between the film and the fabric through physical and chemical covalent bond interactions.

Benefits of technology

It achieves the effect of simple structure, strong thermal insulation, breathable and moisture-permeable, and comfortable wearing, and improves the bonding fastness between the film and fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119872029A_ABST
    Figure CN119872029A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of textile composite fabrics, in particular to a composite fabric with synergistic warm keeping and heat insulation functions and a preparation method. The fabric is formed by compounding a modified SiO2 electrostatic spinning film, a modified polyurethane coating and a modified warm-keeping yarn fabric, and the prepared fabric is simple in structure, high in warm-keeping and heat-insulating performance, breathable, moisture permeable and comfortable to wear. The membrane and the fabric are combined through physical action and chemical covalent bond interaction, the stripping strength is further improved, and the binding strength between the membrane and the fabric is enhanced. The composite fabric is simple in preparation process and cost-saving, and can be widely applied to the field of warm-keeping and heat-insulating fabrics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile composite fabrics, and in particular to a composite fabric with synergistic warmth preservation and heat insulation and a preparation method thereof. Background Art

[0002] Traditional thermal insulation fabrics have complex structures, which affects wearing comfort; fabrics with simple structures and strong thermal insulation effects need further research.

[0003] The present invention provides a synergistic thermal insulation composite fabric and a preparation method thereof, which can achieve a synergistic thermal insulation effect by combining a SiO2 electrospinning membrane with a thermal insulation yarn fabric.

[0004] The prepared fabric has a simple structure, strong thermal insulation performance, breathable and moisture permeable, and is comfortable to wear. The membrane and the fabric are combined through physical action and chemical covalent bond interaction, the peeling strength is further improved, and the bonding strength between the membrane and the fabric is enhanced. Summary of the invention

[0005] The invention solves the problem that the traditional thermal insulation fabric has a complex structure and is uncomfortable to wear.

[0006] The technical solution adopted by the present invention is as follows: a synergistic thermal insulation composite fabric is formed by a composite of a modified SiO2 electrospinning membrane, a modified polyurethane coating, and a modified thermal insulation yarn fabric.

[0007] The present invention also discloses a method for preparing a synergistically warm and heat-insulating composite fabric, comprising the following steps:

[0008] Step 1, preparation of flexible SiO2 electrospinning membrane:

[0009] The SiO2 electrospinning precursor was subjected to high-voltage electrospinning to prepare polymer / SiO2 hybrid nanofiber membranes, which were then calcined at high temperature to obtain flexible SiO2 electrospinning membranes.

[0010] The SiO2 electrospinning precursor includes a silicon source hydrolyzate and a polymer carrier solution;

[0011] The silicon source hydrolyzate includes a silicon source, deionized water, and a reagent for adjusting pH. The silicon source hydrolyzate is prepared as follows: the silicon source and deionized water are mixed in a molar ratio of 1:10 to 15, an acid solution is added dropwise to adjust the pH, and magnetic stirring is performed at room temperature for 8 to 12 hours until the pH of the silicon source hydrolyzate is adjusted to 4 to 5;

[0012] The polymer carrier solution comprises a polymer carrier and deionized water, wherein the mass fraction of the polymer carrier in the polymer carrier solution is 10% to 15% by weight;

[0013] The silicon source hydrolyzate and the polymer carrier solution are mixed in a mass ratio of 1:1 to 1.5, and stirred vigorously at room temperature for a certain period of time to obtain a clear and transparent electrospinning precursor;

[0014] Step 2: Use silane coupling agent to modify the SiO2 electrospinning membrane for hydrophobic treatment:

[0015] A silane coupling agent modification reagent is dissolved in a mixed solvent consisting of deionized water and anhydrous ethanol in a volume ratio of 1:1 to 1.5, and an acidic solution is added dropwise to adjust the pH value of the solution to about 5 to obtain a modified solution;

[0016] The amount of silane coupling agent modification agent is 2% to 5% relative to the mass fraction of SiO2 electrospinning membrane;

[0017] The SiO2 electrospun membrane is immersed in the modified solution and reacted under certain conditions. After the reaction is completed, it is taken out, cleaned with clean water, and dried;

[0018] After modification, the number of hydroxyl groups (-OH) on the surface of SiO2 electrospinning membrane decreased, functional groups of carbon-carbon double bonds (C=C) were introduced on the membrane surface, and the hydrophobicity was improved.

[0019] Step 3, preparation of modified polyurethane coating:

[0020] Preparation of polyurethane coating, the materials include diisocyanate, polyol, chain extender, internal crosslinking agent, modified end-capping agent;

[0021] According to n (isocyanate group): n (hydroxyl group) = 2 to 2.5, diisocyanate, polyol, and 2%wt catalyst relative to the mass of diisocyanate and polyol are added to a mechanical stirring device, the oil bath is heated to 80 to 90°C, and stirred for 2 to 3 hours to carry out a prepolymerization reaction;

[0022] Then, a small molecule chain extender is added at 10% to 15% by weight relative to the mass of the diisocyanate and the polyol, and the temperature is lowered to 50 to 60° C. and reacted for 2 to 3 hours to perform a chain extension reaction;

[0023] Then, a cross-linking agent is added at 0.5% to 1% by weight relative to the mass of the diisocyanate and the polyol to carry out a cross-linking reaction for about 1 hour, and 30% to 40% by weight acetone relative to the mass of the diisocyanate and the polyol is added dropwise during the reaction to adjust the viscosity, wherein the acetone is anhydrous acetone from which water has been removed in advance by using a 4A molecular sieve;

[0024] Next, the end-capping agent is added at a dosage of 20% to 25% wt relative to the diisocyanate, and the reaction is continued for 1 hour. After the end-capping is completed, the isocyanate group is completely reacted as determined by di-n-butylamine titration method, and the temperature is lowered to 40 to 50° C., and then an appropriate amount of deionized water is added to control the solid content of the emulsion to be 30% to 35% wt. The emulsification is carried out at a high speed of 1000 to 1500 r for about 1 hour to obtain a polyurethane coating emulsion modified with a carbon-carbon double bond (C=C);

[0025] Step 4: Preparation of modified warm yarn fabric:

[0026] A vinyl silane coupling agent in a certain proportion relative to the mass of the fabric is weighed and dissolved in a mixed solvent prepared by anhydrous ethanol and deionized water in a volume ratio of 1:1 to 2, and an acid solution is added dropwise to adjust the pH of the solution to about 4 to obtain a coupling agent modified solution;

[0027] The ratio of the vinyl silane coupling agent to the mass of the fabric is 4% to 7% by weight; the volume ratio of the vinyl silane coupling agent to the mixed solvent is 1:30 to 40;

[0028] The thermal insulation yarn fabric is immersed in a vinyl silane coupling agent modified solution and allowed to stand at room temperature for 24 to 48 hours to react; after the reaction is completed, the fabric is taken out, rinsed with deionized water for multiple times to wash away excess silane coupling agent, and dried to obtain a thermal insulation yarn fabric modified by a vinyl silane coupling agent. The specific reaction mechanism is: under acidic conditions, the vinyl silane coupling agent first undergoes a hydrolysis reaction to generate silanol, and then undergoes a dehydration condensation reaction with the hydroxyl group on the sugar ring structure on the seaweed polysaccharide molecular chain on the fabric surface to be grafted onto the fabric surface;

[0029] Step 5: Preparation of synergistic thermal insulation composite fabric:

[0030] Weigh a certain amount of modified warm yarn fabric and the same area of ​​modified SiO2 electrospinning membrane;

[0031] An initiator is added according to 0.5% to 1% wt of the mass fraction of the polyurethane coating emulsion and stirred evenly. The modified polyurethane coating emulsion is weighed according to a mass fraction of 10% to 15% wt (relative to the total mass of the fabric and the SiO2 electrospinning membrane). The three are compounded through a high-temperature lamination process to prepare a synergistic thermal insulation composite fabric.

[0032] Furthermore, in step 1, the silicon source is tetraethyl orthosilicate (TEOS) or tetraethyl orthosilicate (TEOS).

[0033] Furthermore, in step 1, the polymer carrier is one of polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), and polystyrene (PS).

[0034] Furthermore, in step 1, the reagent used to adjust the pH is one of dilute hydrochloric acid (HCl), acetic acid (CH3CH2COOH), and phosphoric acid (H3PO4).

[0035] Furthermore, in step 1, the silicon source hydrolyzate and the polymer carrier solution are mixed and stirred for 4 to 6 hours.

[0036] Furthermore, in step one, the high-voltage electrospinning process applies a voltage of 25 to 30 kV, an infusion speed of 1 mL / h, a receiving distance of 18 to 25 cm, an ambient temperature of 23 to 27° C., an ambient humidity of 42% to 48%, and a receiving drum speed of 50 rpm.

[0037] Furthermore, in step 1, the high temperature calcination process places the hybrid nanofiber membrane in a muffle furnace and calcines it at 600-800° C. for 0.5-1 h to remove the organic polymer carrier.

[0038] Furthermore, in step 2, the silane coupling agent modification reagent is one of vinyl triethoxysilane, vinyl tri (β-methoxyethoxy) silane, and γ-methacryloxypropyl trimethoxy silane (KH-570).

[0039] Furthermore, in step 2, the acidic solution used to adjust the pH of the solution is one of dilute hydrochloric acid, acetic acid, and phosphoric acid.

[0040] Furthermore, in step 2, the reaction conditions are a temperature of 70 to 80° C. and a reaction time of 6 to 8 hours.

[0041] Furthermore, in step three, the diisocyanate is one of toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), etc.

[0042] Further, in step 3, the polyol includes one or more of polyester polyol or polyether polyol, and polyester polyol includes polyethylene adipate glycol (PEA), polyethylene adipate glycol-propylene glycol ester glycol, polyethylene adipate-diethylene glycol ester glycol (PDA), polyethylene adipate glycol-diethylene glycol ester glycol, etc. Polyether polyol includes polyethylene glycol, polypropylene glycol (PPG), polytetramethylene glycol (PTHF), polytetramethylene glycol-propylene oxide copolymer glycol, etc.

[0043] Furthermore, in step three, the catalyst is dibutyltin dilaurate (DBTDL).

[0044] Furthermore, in step three, the chain extender is one or two of propylene glycol (PG), 1,4-butanediol (BDO), dimethylolpropionic acid (DMPA), and diethanolamine (DEA).

[0045] Furthermore, in step three, the internal cross-linking agent is one of trimethylolpropane (TMP), triethanolamine (TEA), and pentaerythritol (PE).

[0046] Furthermore, in step three, the end-capping agent is one of hydroxyethyl acrylate (HEA), hydroxyethyl methacrylate (HEMA), hydroxypropyl methacrylate (2HPMA), acrylamide (AM), methacrylamide (MAM), and aminopolyethylene glycol acrylamide (AM).

[0047] Furthermore, in step 4, the vinyl silane coupling agent is one of vinyl triethoxy silane, vinyl tri (β-methoxyethoxy) silane, and γ-methacryloxypropyl trimethoxy silane (KH-570).

[0048] Furthermore, in step 4, the proportion of the vinyl silane coupling agent relative to the mass of the fabric is 4% to 7% by weight, and the volume ratio of the vinyl silane coupling agent to the mixed solvent is 1:30 to 40.

[0049] Furthermore, in step 4, the acid solution used to adjust the solution is one of dilute hydrochloric acid, acetic acid, and phosphoric acid.

[0050] Furthermore, in step four, the warm yarn fabric is a plain woven fabric woven with warp and weft yarns of polyester 150D / 144F semi-bright light mesh, a plain woven fabric woven with warp and weft yarns of nylon 20D / 24F semi-bright FDY, or a plain woven fabric woven with warp and weft yarns of nylon 70D / 68F semi-bright DTY.

[0051] Furthermore, in step five, the initiator is potassium persulfate (KPS).

[0052] The beneficial effects achieved by the present invention using the above structure are as follows:

[0053] 1. The combination of SiO2 electrospinning membrane and thermal yarn fabric can play a synergistic role in warmth and insulation;

[0054] 2. The membrane and fabric are combined through physical action and chemical covalent bond interaction, the peeling strength is further improved, and the bonding strength between the membrane and fabric is enhanced;

[0055] 3. The composite fabric preparation process is simple and cost-saving, and can be widely used in the field of thermal insulation fabrics;

[0056] 4. The prepared fabric has a simple structure, strong thermal insulation performance, is breathable and moisture-permeable, and is comfortable to wear. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0058] Figure 1 Schematic diagram of the structure of the composite fabric of this scheme;

[0059] Figure 2 is the hydrolysis reaction formula of tetraethyl orthosilicate (TEOS) in Example 2;

[0060] Figure 3 is the reaction formula for modification of SiO2 electrospinning membrane in Example 2;

[0061] Figure 4 is the polyurethane modification reaction formula in Example 2;

[0062] Figure 5 This is the reaction formula of the seaweed polysaccharide component and the silane coupling agent in the warm yarn in Example 2. DETAILED DESCRIPTION

[0063] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0064] Embodiment 1:

[0065] Step 1, preparation of flexible SiO2 electrospinning membrane:

[0066] Select tetraethyl orthosilicate (TEOS) as the silicon source, weigh 20.8g of tetraethyl orthosilicate (TEOS) and mix it with 20g of deionized water, add dilute hydrochloric acid solution to adjust the pH to 4.5, stir magnetically at room temperature for 8h, and wait until the hydrolysis and polymerization are complete to obtain a silicon source hydrolyzate;

[0067] Weigh 10 g of polyvinyl alcohol (PVA) and 90 g of deionized water and mix and stir at room temperature to obtain a polymer carrier solution;

[0068] 20g of silicon source hydrolyzate and 20g of polymer carrier solution were vigorously stirred at room temperature until clear and transparent to obtain electrospinning solution;

[0069] Set the voltage to 30kv, the perfusion speed to 1mL / h, the receiving distance to 18cm, the ambient temperature to 24±2℃, the ambient humidity to 45±2%, and the receiving drum speed to 50rpm. After the end, remove the SiO2 electrospun membrane from the drum, and place the electrospun membrane in a muffle furnace and calcine it at 600℃ for 0.5h to obtain a flexible SiO2 electrospun membrane.

[0070] Step 2: Use silane coupling agent to modify the SiO2 electrospinning membrane for hydrophobic treatment:

[0071] Add 0.2 g of γ-methacryloxypropyltrimethoxysilane (KH-570) to a uniform mixture of 15 mL of deionized water and 15 mL of anhydrous ethanol, stir evenly, and add dilute hydrochloric acid solution to adjust the pH to about 5;

[0072] 10g of flexible SiO2 electrospinning membrane was immersed in the silane coupling agent modified solution, reacted at 70°C for 4h, taken out after the reaction, repeatedly washed with deionized water, and dried to obtain the modified SiO2 electrospinning membrane;

[0073] Step 3, preparation of modified polyurethane coating:

[0074] Weigh 22.2 g of isophorone diisocyanate (IPDI), 20 g of polypropylene glycol 400 (PEG400), and 0.84 g of catalyst dibutyltin dilaurate (DBTDL) and stir them in an oil bath at 80 °C for 2 h with a mechanical stirring device, add 2.11 g of 1,4-butanediol (BDO) and 2.11 g of diethanolamine (DEA) as a small molecule chain extender to carry out a chain extension reaction, and cool to 60 °C for 2 h;

[0075] Then, 0.4 g of internal crosslinking agent trimethylolpropane (TMP) was added to react for 1 h, and 12.66 g of acetone was added dropwise during the reaction to control the viscosity of the system;

[0076] Next, 4.44 g of sodium bisulfite (NaHSO3) was added to carry out the end-capping reaction for 1 hour. After the end-capping was completed, the isocyanate group was determined to be completely reacted by di-n-butylamine titration method, and the temperature was lowered to 50°C. Then, 120 mL of deionized water was added to control the solid content to about 30%, and the mixture was emulsified at a high speed of 1000 rpm for about 1 hour to prepare a common polyurethane coating emulsion.

[0077] Step 4: Preparation of modified warm yarn fabric:

[0078] Take 20g of plain woven fabric with warp and weft yarns of polyester 150D / 144F semi-gloss light mesh;

[0079] Weigh 15 mL of deionized water and 15 mL of anhydrous ethanol in equal volumes and mix them evenly; weigh 0.8 g of γ-methacryloxypropyltrimethoxysilane (KH-570) and completely dissolve it in the mixed solvent; drop dilute hydrochloric acid to adjust the pH of the solution to about 4; immerse the fabric completely in the silane coupling agent modified solution; leave it at room temperature in the dark for about 48 hours; after the reaction is completed, rinse with a large amount of deionized water to remove the unreacted monomers; dry it to obtain a modified warm yarn fabric;

[0080] Step 5: Preparation of synergistic thermal insulation composite fabric:

[0081] Take 20cm×20cm modified thermal yarn fabric and modified SiO2 electrospinning membrane of the same area, with a total mass of about 26g. Take 2.6g of polyurethane emulsion and compound it with the modified thermal yarn fabric and modified SiO2 electrospinning membrane through a 90℃ high-temperature lamination process to prepare a synergistic thermal composite fabric.

[0082] Embodiment 2:

[0083] Step 1, preparation of flexible SiO2 electrospinning membrane:

[0084] Select tetraethyl orthosilicate (TEOS) as the silicon source, weigh 20.8g of tetraethyl orthosilicate (TEOS) and mix it with 20g of deionized water, add dilute hydrochloric acid solution to adjust the pH to 4.5, and stir magnetically for 8h at room temperature until the hydrolysis and polymerization are complete to obtain a silicon source hydrolyzate. The hydrolysis of tetraethyl orthosilicate (TEOS) is as follows: Figure 2 As shown;

[0085] Weigh 10 g of polyvinyl alcohol (PVA) and 90 g of deionized water and mix and stir at room temperature to obtain a polymer carrier solution;

[0086] 20g of silicon source hydrolyzate and 20g of polymer carrier solution were vigorously stirred at room temperature until clear and transparent to obtain electrospinning solution;

[0087] Set the voltage to 30kv, the perfusion speed to 1mL / h, the receiving distance to 18cm, the ambient temperature to 24±2℃, the ambient humidity to 45±2%, and the receiving drum speed to 50rpm. After the end, remove the SiO2 electrospun membrane from the drum, and place the electrospun membrane in a muffle furnace and calcine it at 600℃ for 0.5h to obtain a flexible SiO2 electrospun membrane.

[0088] Step 2: Use silane coupling agent to modify the SiO2 electrospinning membrane for hydrophobic treatment

[0089] Add 0.2 g of γ-methacryloxypropyltrimethoxysilane (KH-570) to a uniform mixture of 15 mL of deionized water and 15 mL of anhydrous ethanol, stir evenly, and add dilute hydrochloric acid solution to adjust the pH to about 5;

[0090] 10g of flexible SiO2 electrospinning membrane was immersed in the silane coupling agent modified solution and reacted at 70℃ for 4h. After the reaction, it was taken out and repeatedly washed with deionized water and dried to obtain the modified SiO2 electrospinning membrane. The modification principle of SiO2 electrospinning membrane is as follows: Figure 3 As shown;

[0091] Step 3, preparation of modified polyurethane coating:

[0092] Weigh 22.2 g of isophorone diisocyanate (IPDI), 20 g of polypropylene glycol 400 (PEG400), and 0.84 g of catalyst dibutyltin dilaurate (DBTDL) and stir them in an oil bath at 80 °C for 2 h with a mechanical stirring device, add 2.11 g of 1,4-butanediol (BDO) and 2.11 g of diethanolamine (DEA) as a small molecule chain extender to carry out a chain extension reaction, and cool to 60 °C for 2 h;

[0093] Then, 0.4 g of internal crosslinking agent trimethylolpropane (TMP) was added to react for 1 h, and 12.66 g of acetone was added dropwise during the reaction to control the viscosity of the system;

[0094] Next, 4.44 g of acrylamide (AM) was added to carry out the end-capping reaction for 1 hour. After the end-capping was completed, the temperature was lowered to 50°C after confirming that the isocyanate group was completely reacted by di-n-butylamine titration method. Then, 120 mL of deionized water was added to control the solid content to about 30%. The mixture was stirred at a high speed of 1000 rpm for about 1 hour to prepare a polyurethane coating emulsion modified with a carbon-carbon double bond (C=C). The polyurethane modification principle diagram is shown in FIG. Figure 4 As shown;

[0095] Step 4: Preparation of modified warm yarn fabric:

[0096] Take 20g of plain woven fabric with warp and weft yarns of polyester 150D / 144F semi-gloss light mesh;

[0097] Weigh 15 mL of deionized water and 15 mL of anhydrous ethanol in equal volumes and mix them evenly. Weigh 0.8 g of γ-methacryloxypropyltrimethoxysilane (KH-570) and completely dissolve it in the mixed solvent. Add dilute hydrochloric acid to adjust the pH of the solution to about 4. Immerse the fabric completely in the silane coupling agent modified solution and keep it at room temperature in the dark for about 48 hours. After the reaction is completed, rinse with a large amount of deionized water to remove the unreacted monomers and dry it to obtain a modified warm yarn fabric. The reaction principle of the seaweed polysaccharide component in the warm yarn and the silane coupling agent is as follows: Figure 5 As shown;

[0098] Step 5: Preparation of synergistic thermal insulation composite fabric:

[0099] Add 0.005 g of thermal initiator potassium persulfate (KPS) into 10 mL of polyurethane coating emulsion and stir evenly;

[0100] Take 20cm×20cm modified thermal insulation yarn fabric and modified SiO2 electrospinning membrane of the same area, with a total mass of about 26g, take 2.6g polyurethane emulsion and modified thermal insulation yarn fabric and modified SiO2 electrospinning membrane through 90℃ high temperature lamination process to prepare synergistic thermal insulation composite fabric. The composite fabric structure is shown in Figure 1 As shown;

[0101] Embodiment 3:

[0102] Step 1, preparation of flexible SiO2 electrospinning membrane:

[0103] Select tetraethyl orthosilicate (TEOS) as the silicon source, weigh 20.8g of tetraethyl orthosilicate (TEOS) and mix it with 20g of deionized water, add dilute hydrochloric acid solution to adjust the pH to 4.5, stir magnetically at room temperature for 8h, and wait until the hydrolysis and polymerization are complete to obtain a silicon source hydrolyzate;

[0104] Weigh 10 g of polyvinyl alcohol (PVA) and 90 g of deionized water and mix and stir at room temperature to obtain a polymer carrier solution;

[0105] 20g of silicon source hydrolyzate and 20g of polymer carrier solution were vigorously stirred at room temperature until clear and transparent to obtain electrospinning solution;

[0106] Set the voltage to 30kv, the perfusion speed to 1mL / h, the receiving distance to 18cm, the ambient temperature to 24±2℃, the ambient humidity to 45±2%, and the receiving drum speed to 50rpm. After the end, remove the SiO2 electrospun membrane from the drum, and place the electrospun membrane in a muffle furnace and calcine it at 600℃ for 0.5h to obtain a flexible SiO2 electrospun membrane.

[0107] Step 2: Use silane coupling agent to modify the SiO2 electrospinning membrane for hydrophobic treatment:

[0108] Add 0.3 g of γ-methacryloxypropyltrimethoxysilane (KH-570) to a uniform mixture of 15 mL of deionized water and 15 mL of anhydrous ethanol, stir evenly, and add dilute hydrochloric acid solution to adjust the pH to about 5;

[0109] 10g of flexible SiO2 electrospinning membrane was immersed in the silane coupling agent modified solution, reacted at 70°C for 4h, taken out after the reaction, repeatedly washed with deionized water, and dried to obtain the modified SiO2 electrospinning membrane;

[0110] Step 3, preparation of modified polyurethane coating:

[0111] Weigh 22.2 g of isophorone diisocyanate (IPDI), 20 g of polypropylene glycol 400 (PEG400), and 0.84 g of catalyst dibutyltin dilaurate (DBTDL) and stir them in an oil bath at 80 °C for 2 h with a mechanical stirring device, add 2.11 g of 1,4-butanediol (BDO) and 2.11 g of diethanolamine (DEA) as a small molecule chain extender to carry out a chain extension reaction, and cool to 60 °C for 2 h;

[0112] Then, 0.4 g of internal crosslinking agent trimethylolpropane (TMP) was added to react for 1 h, and 12.66 g of acetone was added dropwise during the reaction to control the viscosity of the system;

[0113] Next, 4.44 g of acrylamide (AM) was added to carry out the end-capping reaction for 1 hour. After the end-capping was completed, the temperature was lowered to 50° C. after confirming that the isocyanate group was completely reacted by di-n-butylamine titration method. Then, 120 mL of deionized water was added to control the solid content to about 30%. The mixture was stirred at 1000 rpm for about 1 hour to prepare a polyurethane coating emulsion modified with a carbon-carbon double bond (C=C).

[0114] Step 4: Preparation of modified warm yarn fabric:

[0115] Take 20g of plain woven fabric with warp and weft yarns of polyester 150D / 144F semi-gloss light mesh;

[0116] Weigh 15 mL of deionized water and 15 mL of anhydrous ethanol in equal volumes and mix them evenly; weigh 1 g of γ-methacryloxypropyltrimethoxysilane (KH-570) and completely dissolve it in the mixed solvent; drop dilute hydrochloric acid to adjust the pH of the solution to about 4; completely immerse the fabric in the silane coupling agent modified solution; and stand it at room temperature in the dark for about 48 hours. After the reaction is completed, rinse with a large amount of deionized water to remove the unreacted monomers, and dry it to obtain a modified warm yarn fabric;

[0117] Step 5: Preparation of synergistic thermal insulation composite fabric:

[0118] Add 0.005 g of thermal initiator potassium persulfate (KPS) into 10 mL of polyurethane coating emulsion and stir evenly;

[0119] Take 20cm×20cm modified thermal yarn fabric and modified SiO2 electrospinning membrane of the same area, with a total mass of about 26g. Take 2.6g of polyurethane emulsion and compound it with the modified thermal yarn fabric and modified SiO2 electrospinning membrane through a 90℃ high-temperature lamination process to prepare a synergistic thermal composite fabric.

[0120] Embodiment 4:

[0121] Step 1, preparation of flexible SiO2 electrospinning membrane:

[0122] Select tetraethyl orthosilicate (TEOS) as the silicon source, weigh 20.8g of tetraethyl orthosilicate (TEOS) and mix it with 20g of deionized water, add dilute hydrochloric acid solution to adjust the pH to 4.5, stir magnetically at room temperature for 8h, and wait until the hydrolysis and polymerization are complete to obtain a silicon source hydrolyzate;

[0123] Weigh 10 g of polyvinyl alcohol (PVA) and 90 g of deionized water and mix and stir at room temperature to obtain a polymer carrier solution;

[0124] 20g of silicon source hydrolyzate and 20g of polymer carrier solution were vigorously stirred at room temperature until clear and transparent to obtain electrospinning solution;

[0125] Set the voltage to 30kv, the perfusion speed to 1mL / h, the receiving distance to 18cm, the ambient temperature to 24±2℃, the ambient humidity to 45±2%, and the receiving drum speed to 50rpm. After the end, remove the SiO2 electrospun membrane from the drum, and place the electrospun membrane in a muffle furnace and calcine it at 600℃ for 0.5h to obtain a flexible SiO2 electrospun membrane.

[0126] Step 2: Use silane coupling agent to modify the SiO2 electrospinning membrane for hydrophobic treatment:

[0127] Add 0.4 g of γ-methacryloxypropyltrimethoxysilane (KH-570) to a uniform mixture of 15 mL of deionized water and 15 mL of anhydrous ethanol, stir evenly, and add dilute hydrochloric acid solution to adjust the pH to about 5;

[0128] 10g of flexible SiO2 electrospinning membrane was immersed in the silane coupling agent modified solution, reacted at 70°C for 4h, taken out after the reaction, repeatedly washed with deionized water, and dried to obtain the modified SiO2 electrospinning membrane;

[0129] Step 3, preparation of modified polyurethane coating:

[0130] Weigh 22.2 g of isophorone diisocyanate (IPDI), 20 g of polypropylene glycol 400 (PEG400), and 0.84 g of catalyst dibutyltin dilaurate (DBTDL) and stir them in an oil bath at 80 °C for 2 h with a mechanical stirring device, add 2.11 g of 1,4-butanediol (BDO) and 2.11 g of diethanolamine (DEA) as a small molecule chain extender to carry out a chain extension reaction, and cool to 60 °C for 2 h;

[0131] Then, 0.4 g of internal crosslinking agent trimethylolpropane (TMP) was added to react for 1 h, and 12.66 g of acetone was added dropwise during the reaction to control the viscosity of the system;

[0132] Next, 4.44 g of acrylamide (AM) was added to carry out the end-capping reaction for 1 hour. After the end-capping was completed, the temperature was lowered to 50° C. after confirming that the isocyanate group was completely reacted by di-n-butylamine titration method. Then, 120 mL of deionized water was added to control the solid content to about 30%. The mixture was stirred at 1000 rpm for about 1 hour to prepare a polyurethane coating emulsion modified with a carbon-carbon double bond (C=C).

[0133] Step 4: Preparation of modified warm yarn fabric:

[0134] Take 20g of plain woven fabric with warp and weft yarns of polyester 150D / 144F semi-gloss light mesh;

[0135] Weigh 15 mL of deionized water and 15 mL of anhydrous ethanol in equal volumes and mix them evenly; weigh 1.2 g of γ-methacryloxypropyltrimethoxysilane (KH-570) and completely dissolve it in the mixed solvent; drop dilute hydrochloric acid to adjust the pH of the solution to about 4; completely immerse the fabric in the silane coupling agent modified solution; stand it at room temperature in the dark for about 48 hours; after the reaction is completed, rinse it with a large amount of deionized water to remove the unreacted monomers; and dry it to obtain a modified warm yarn fabric;

[0136] Step 5: Preparation of synergistic thermal insulation composite fabric:

[0137] Add 0.005 g of thermal initiator potassium persulfate (KPS) into 10 mL of polyurethane coating emulsion and stir evenly;

[0138] Take 20cm×20cm modified thermal yarn fabric and modified SiO2 electrospinning membrane of the same area, with a total mass of about 26g. Take 2.6g of polyurethane emulsion and compound it with the modified thermal yarn fabric and modified SiO2 electrospinning membrane through a 90℃ high-temperature lamination process to prepare a synergistic thermal composite fabric.

[0139] Embodiment 5:

[0140] Step 1, preparation of flexible SiO2 electrospinning membrane:

[0141] Select tetraethyl orthosilicate (TEOS) as the silicon source, weigh 20.8g of tetraethyl orthosilicate (TEOS) and mix it with 20g of deionized water, add dilute hydrochloric acid solution to adjust the pH to 4.5, stir magnetically at room temperature for 8h, and wait until the hydrolysis and polymerization are complete to obtain a silicon source hydrolyzate;

[0142] Weigh 10 g of polyvinyl alcohol (PVA) and 90 g of deionized water and mix and stir at room temperature to obtain a polymer carrier solution;

[0143] 20g of silicon source hydrolyzate and 20g of polymer carrier solution were vigorously stirred at room temperature until clear and transparent to obtain electrospinning solution;

[0144] Set the voltage to 30kv, the perfusion speed to 1mL / h, the receiving distance to 18cm, the ambient temperature to 24±2℃, the ambient humidity to 45±2%, and the receiving drum speed to 50rpm. After completion, remove the SiO2 electrospun membrane from the drum. Place the electrospun membrane in a muffle furnace and calcine it at 600℃ for 0.5h to obtain a flexible SiO2 electrospun membrane.

[0145] Step 2: Use silane coupling agent to modify the SiO2 electrospinning membrane for hydrophobic treatment:

[0146] Add 0.5 g of γ-methacryloxypropyltrimethoxysilane (KH-570) to a uniform mixture of 15 mL of deionized water and 15 mL of anhydrous ethanol, stir evenly, and add dilute hydrochloric acid solution to adjust the pH to about 5;

[0147] 10g of flexible SiO2 electrospinning membrane was immersed in the silane coupling agent modified solution and reacted at 70℃ for 4h. After the reaction, it was taken out, repeatedly washed with deionized water, and dried to obtain the modified SiO2 electrospinning membrane;

[0148] Step 3, preparation of modified polyurethane coating:

[0149] Weigh 22.2 g of isophorone diisocyanate (IPDI), 20 g of polypropylene glycol 400 (PEG400), and 0.84 g of catalyst dibutyltin dilaurate (DBTDL) and stir them in an oil bath at 80 °C for 2 h with a mechanical stirring device, add 2.11 g of 1,4-butanediol (BDO) and 2.11 g of diethanolamine (DEA) as a small molecule chain extender to carry out a chain extension reaction, and cool to 60 °C for 2 h;

[0150] Then, 0.4 g of internal crosslinking agent trimethylolpropane (TMP) was added to react for 1 h, and 12.66 g of acetone was added dropwise during the reaction to control the viscosity of the system;

[0151] Next, 4.44 g of acrylamide (AM) was added to carry out the end-capping reaction for 1 h. After the end-capping was completed, the temperature was lowered to 50 °C after confirming that the isocyanate groups were completely reacted using di-n-butylamine titration;

[0152] Then, 120 mL of deionized water was added to control the solid content to about 30%, and the mixture was stirred and emulsified at a high speed of 1000 rpm for about 1 hour to prepare a polyurethane coating emulsion modified with a carbon-carbon double bond (C=C);

[0153] Step 4: Preparation of modified warm yarn fabric:

[0154] Take 20g of plain woven fabric with warp and weft yarns of polyester 150D / 144F semi-gloss light mesh;

[0155] Weigh 15 mL of deionized water and 15 mL of anhydrous ethanol in equal volumes and mix them evenly; weigh 1.4 g of γ-methacryloxypropyltrimethoxysilane (KH-570) and completely dissolve it in the mixed solvent; drop dilute hydrochloric acid to adjust the pH of the solution to about 4; completely immerse the fabric in the silane coupling agent modified solution; stand it at room temperature in the dark for about 48 hours; after the reaction is completed, rinse it with a large amount of deionized water to remove the unreacted monomers; dry it to obtain a modified warm yarn fabric;

[0156] Step 5: Preparation of synergistic thermal insulation composite fabric:

[0157] Add 0.005 g of thermal initiator potassium persulfate (KPS) into 10 mL of polyurethane coating emulsion and stir evenly;

[0158] Take 20cm×20cm modified thermal yarn fabric and modified SiO2 electrospinning membrane of the same area, with a total mass of about 26g. Take 2.6g of polyurethane emulsion and compound it with the modified thermal yarn fabric and modified SiO2 electrospinning membrane through a 90℃ high-temperature lamination process to prepare a synergistic thermal composite fabric.

[0159] Embodiment 6:

[0160] Step 1, preparation of flexible SiO2 electrospinning membrane:

[0161] Select tetraethyl orthosilicate (TEOS) as the silicon source, weigh 20.8g of tetraethyl orthosilicate (TEOS) and mix it with 20g of deionized water, add dilute hydrochloric acid solution to adjust the pH to 4.5, stir magnetically at room temperature for 8h, and wait until the hydrolysis and polymerization are complete to obtain a silicon source hydrolyzate;

[0162] Weigh 10 g of polyvinyl alcohol (PVA) and 90 g of deionized water and mix and stir at room temperature to obtain a polymer carrier solution;

[0163] 20g of silicon source hydrolyzate and 20g of polymer carrier solution were vigorously stirred at room temperature until clear and transparent to obtain electrospinning solution;

[0164] Set the voltage to 30kv, the perfusion speed to 1mL / h, the receiving distance to 18cm, the ambient temperature to 24±2℃, the ambient humidity to 45±2%, and the receiving drum speed to 50rpm. After the end, remove the SiO2 electrospun membrane from the drum, and place the electrospun membrane in a muffle furnace and calcine it at 600℃ for 0.5h to obtain a flexible SiO2 electrospun membrane.

[0165] Step 2: Use silane coupling agent to modify the SiO2 electrospinning membrane for hydrophobic treatment

[0166] Add 0.3 g of γ-methacryloxypropyltrimethoxysilane (KH-570) to a uniform mixture of 15 mL of deionized water and 15 mL of anhydrous ethanol, stir evenly, and add dilute hydrochloric acid solution to adjust the pH to about 5;

[0167] 10g of flexible SiO2 electrospinning membrane was immersed in the silane coupling agent modified solution, reacted at 70°C for 4h, taken out after the reaction, repeatedly washed with deionized water, and dried to obtain the modified SiO2 electrospinning membrane;

[0168] Step 3, preparation of modified polyurethane coating:

[0169] Weigh 22.2 g of isophorone diisocyanate (IPDI), 20 g of polypropylene glycol 400 (PEG400), and 0.84 g of catalyst dibutyltin dilaurate (DBTDL) and stir them in an oil bath at 80 °C for 2 h with a mechanical stirring device, add 2.11 g of 1,4-butanediol (BDO) and 2.11 g of diethanolamine (DEA) as a small molecule chain extender to carry out a chain extension reaction, and cool to 60 °C for 2 h;

[0170] Then, 0.4 g of internal crosslinking agent trimethylolpropane (TMP) was added to react for 1 h, and 12.66 g of acetone was added dropwise during the reaction to control the viscosity of the system;

[0171] Next, 4.44 g of acrylamide (AM) was added to carry out the end-capping reaction for 1 h. After the end-capping was completed, the temperature was lowered to 50 °C after confirming that the isocyanate groups were completely reacted using di-n-butylamine titration;

[0172] Then, 95 mL of deionized water was added to control the solid content to about 35%, and the mixture was stirred and emulsified at a high speed of 1000 rpm for about 1 hour to prepare a polyurethane coating emulsion modified with a carbon-carbon double bond (C=C);

[0173] Step 4: Preparation of modified warm yarn fabric:

[0174] Take 20g of plain woven fabric with warp and weft yarns of polyester 150D / 144F semi-gloss light mesh;

[0175] Weigh 15 mL of deionized water and 15 mL of anhydrous ethanol in equal volumes and mix them evenly; weigh 1 g of γ-methacryloxypropyltrimethoxysilane (KH-570) and completely dissolve it in the mixed solvent; drop dilute hydrochloric acid to adjust the pH of the solution to about 4; completely immerse the fabric in the silane coupling agent modified solution; and stand it at room temperature in the dark for about 48 hours. After the reaction is completed, rinse with a large amount of deionized water to remove the unreacted monomers, and dry it to obtain a modified warm yarn fabric;

[0176] Step 5: Preparation of synergistic thermal insulation composite fabric:

[0177] Add 0.005 g of thermal initiator potassium persulfate (KPS) into 10 mL of polyurethane coating emulsion and stir evenly;

[0178] Take 20cm×20cm modified thermal yarn fabric and modified SiO2 electrospinning membrane of the same area, with a total mass of about 26g. Take 2.6g of polyurethane emulsion and compound it with the modified thermal yarn fabric and modified SiO2 electrospinning membrane through a 90℃ high-temperature lamination process to prepare a synergistic thermal composite fabric.

[0179] The warp and weft peel strength of the composite fabric tested according to FZ / T80007.1 is shown in Table 1, which is 4.2N / 4.3N for Example 1, 6.8N / 6.5N for Example 2, 7.5N / 7.8N for Example 3, 7.9N / 8.0N for Example 4, 8.5N / 8.6N for Example 5, and 8.1N / 8.2N for Example 6.

[0180] Table 1: Warp and weft peel strength of each example

[0181] Experimental samples Warp peel strength (N) Weft peel strength (N) Example 1 4.2 4.3 Example 2 6.8 6.5 Example 3 7.5 7.8 Example 4 7.9 8.0 Example 5 8.5 8.6 Example 6 8.1 8.2

[0182] After the polyurethane coating is modified by carbon-carbon double bond grafting, the bonding strength between SiO2 electrospinning membrane and modified fabric through polyurethane is significantly improved. As the amount of modified silane coupling agent gradually increases or the solid content of modified polyurethane increases, the functional groups participating in the free radical polymerization reaction increase, the covalent chemical bond effect increases, the cohesion of each layer increases, and the peeling strength is improved.

[0183] According to FZ / T73002-2019, the heat transfer coefficient of the fabric is tested. The heat transfer coefficients of the fabric without composite SiO2 electrospinning membrane and each embodiment are shown in Table 2. The uncompounded control sample is 20.43 W / m2·℃, Example 1 is 16.32 W / m2·℃, Example 2 is 16.34 W / m2·℃, Example 3 is 16.38 W / m2·℃, Example 4 is 15.98 W / m2·℃, Example 5 is 16.11 W / m2·℃, and Example 6 is 15.16 W / m2·℃. After compounding, the synergistic warming effect is significantly enhanced.

[0184] Table 2: Thermal conductivity of electrospinning membrane without composite SiO2 and various examples

[0185] Experimental samples <![CDATA[Heat transfer coefficient (W / m 2· ℃)]]> Warm yarn fabric 20.43 Example 1 16.32 Example 2 16.34 Example 3 16.38 Example 4 15.98 Example 5 16.11 Example 6 15.16

[0186] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0187] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite fabric for synergistic warmth preservation and heat insulation, characterized in that: It is formed by a composite of modified SiO2 electrospinning membrane, modified polyurethane coating and modified thermal insulation yarn fabric.

2. The method for preparing a synergistic thermal insulation composite fabric according to claim 1, characterized in that: The method comprises the following steps: Step 1, preparation of a flexible SiO2 electrospinning membrane: The SiO2 electrospinning precursor was subjected to high-voltage electrospinning to prepare polymer / SiO2 hybrid nanofiber membranes, which were then calcined at high temperature to obtain flexible SiO2 electrospinning membranes. The SiO2 electrospinning precursor includes a silicon source hydrolyzate and a polymer carrier solution; The silicon source hydrolyzate includes a silicon source, deionized water, and a reagent for adjusting pH; The polymer carrier solution includes a polymer carrier and deionized water; The silicon source hydrolyzate and the polymer carrier solution are mixed in a mass ratio of 1:1 to 1.5, and stirred vigorously at room temperature to obtain a clear and transparent electrospinning precursor; Step 2: Use silane coupling agent to modify the SiO2 electrospinning membrane for hydrophobic treatment: A silane coupling agent modification reagent is dissolved in a mixed solvent consisting of deionized water and anhydrous ethanol, and an acidic solution is added dropwise to adjust the pH value of the solution to 5 to obtain a modified solution; The SiO2 electrospun membrane is immersed in the modified solution for reaction, taken out after the reaction is completed, cleaned with clean water, and dried; After modification, the number of hydroxyl groups on the surface of SiO2 electrospinning membrane decreased, functional carbon-carbon double bonds were introduced into the membrane surface, and the hydrophobic property was improved. Step 3, preparation of modified polyurethane coating: Preparation of polyurethane coating, the materials include diisocyanate, polyol, chain extender, internal crosslinking agent, modified end-capping agent; According to the ratio of isocyanate group to hydroxyl group, diisocyanate and polyol are measured, and 2%wt catalyst relative to the mass of diisocyanate and polyol is added to a mechanical stirring device, the oil bath is heated to 80-90°C, and stirred for 2-3h to carry out prepolymerization reaction; Then, a small molecule chain extender is added at 10% to 15% by weight relative to the mass of the diisocyanate and the polyol, and the temperature is lowered to 50 to 60° C. and reacted for 2 to 3 hours to perform a chain extension reaction; Then, a cross-linking agent is added at 0.5% to 1% by weight relative to the mass of the diisocyanate and the polyol to carry out a cross-linking reaction for about 1 hour, and 30% to 40% by weight acetone relative to the mass of the diisocyanate and the polyol is added dropwise during the reaction to adjust the viscosity, wherein the acetone is anhydrous acetone from which water has been removed in advance by using a 4A molecular sieve; Next, the end-capping agent is added at a dosage of 20% to 25% wt relative to the diisocyanate, and the reaction is continued for 1 hour. After the end-capping is completed, the isocyanate group is completely reacted as determined by di-n-butylamine titration method, and the temperature is lowered to 40 to 50° C., and then an appropriate amount of deionized water is added to control the solid content of the emulsion to be 30% to 35% wt. The emulsification is carried out at a high speed of 1000 to 1500 r for about 1 hour to obtain a carbon-carbon double bond modified polyurethane coating emulsion; Step 4: Preparation of modified warm yarn fabric: A vinyl silane coupling agent in a certain proportion relative to the mass of the fabric is weighed and dissolved in a mixed solvent of anhydrous ethanol and deionized water, and an acid solution is added dropwise to adjust the pH of the solution to 4 to obtain a coupling agent modified solution; The thermal insulation yarn fabric is immersed in a vinyl silane coupling agent modified solution and allowed to stand at room temperature for 24 to 48 hours to react; after the reaction is completed, the fabric is taken out, rinsed with deionized water for multiple times to wash away excess silane coupling agent, and dried to obtain a thermal insulation yarn fabric modified by a vinyl silane coupling agent. The specific reaction mechanism is: under acidic conditions, the vinyl silane coupling agent first undergoes a hydrolysis reaction to generate silanol, and then undergoes a dehydration condensation reaction with the hydroxyl group on the sugar ring structure on the seaweed polysaccharide molecular chain on the fabric surface to be grafted onto the fabric surface; Step 5: Preparation of synergistic thermal insulation composite fabric: Weigh a certain amount of modified warm yarn fabric and the same area of ​​modified SiO2 electrospinning membrane; An initiator is added according to 0.5% to 1% wt of the mass fraction of the polyurethane coating emulsion and stirred evenly. The modified polyurethane coating emulsion is weighed relative to the total mass of the fabric and the SiO2 electrospinning membrane. The three are compounded through a high-temperature lamination process to prepare a synergistic thermal insulation composite fabric.

3. The method for preparing a synergistic thermal insulation composite fabric according to claim 2, characterized in that: In step one: The silicon source hydrolyzate preparation process is as follows: the silicon source and deionized water are mixed in a molar ratio of 1:10 to 15, an acid solution is added dropwise to adjust the pH, and magnetic stirring is performed at room temperature for 8 to 12 hours until the pH of the silicon source hydrolyzate is adjusted to 4 to 5; The mass fraction of the polymer carrier in the polymer carrier solution is 10% to 15%wt.

4. The method for preparing a synergistic thermal insulation composite fabric according to claim 2, characterized in that: In step 2: The deionized water and anhydrous ethanol form a mixed solvent in a volume ratio of 1:1 to 1.5; The amount of the silane coupling agent modification agent is 2% to 5% relative to the mass fraction of the SiO2 electrospinning membrane.

5. The method for preparing a synergistic thermal insulation composite fabric according to claim 2, characterized in that: In step 4: The anhydrous ethanol and deionized water are mixed in a volume ratio of 1:1 to 2 to prepare a mixed solvent; The proportion of the vinyl silane coupling agent to the mass of the fabric is 4% to 7% by weight; the volume ratio of the vinyl silane coupling agent to the mixed solvent is 1:30 to 40.

6. The method for preparing a synergistic thermal insulation composite fabric according to claim 2, characterized in that: In step one: The silicon source is ethyl orthosilicate or tetraethyl orthosilicate; The polymer carrier is one of polyvinyl alcohol, polyvinyl pyrrolidone and polystyrene; The reagent used for adjusting pH is one of dilute hydrochloric acid, acetic acid, and phosphoric acid; The mixing and stirring time of the silicon source hydrolyzate and the polymer carrier solution is 4 to 6 hours; The high-voltage electrospinning process applies a voltage of 25-30 kV, a perfusion speed of 1 mL / h, a receiving distance of 18-25 cm, an ambient temperature of 23-27° C., an ambient humidity of 42%-48%, and a receiving drum speed of 50 rpm; In step 1, the high temperature calcination process places the hybrid nanofiber membrane in a muffle furnace and calcines it at 600-800° C. for 0.5-1 h to remove the organic polymer carrier.

7. The method for preparing a synergistic thermal insulation composite fabric according to claim 2, characterized in that: In step 2: The silane coupling agent modification agent is one of vinyl triethoxysilane, vinyl tri (β-methoxyethoxy) silane, and γ-methacryloxypropyl trimethoxy silane; The acidic solution used to adjust the pH of the solution is one of dilute hydrochloric acid, acetic acid, and phosphoric acid; The reaction conditions are a temperature of 70 to 80° C. and a reaction time of 6 to 8 hours.

8. The method for preparing a synergistic thermal insulation composite fabric according to claim 2, characterized in that: In step three: The diisocyanate is one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, etc.; The catalyst is dibutyltin dilaurate; The internal cross-linking agent is one of trimethylolpropane, triethanolamine and pentaerythritol; In step 3, the end-capping agent is one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, acrylamide, methacrylamide, and aminopolyethylene glycol acrylamide.

9. The method for preparing a synergistic thermal insulation composite fabric according to claim 2, characterized in that: In step 4: The vinyl silane coupling agent is one of vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane, and γ-methacryloxypropyl trimethoxysilane; The acid solution used for adjusting the solution is one of dilute hydrochloric acid, acetic acid, and phosphoric acid; The warm yarn fabric is a plain woven fabric woven with warp and weft yarns of polyester 150D / 144F semi-bright light mesh, a plain woven fabric woven with warp and weft yarns of nylon 20D / 24F semi-bright FDY, and a plain woven fabric woven with warp and weft yarns of nylon 70D / 68F semi-bright DTY.

10. The method for preparing a synergistic thermal insulation composite fabric according to claim 2, characterized in that: In step 5, the initiator is potassium persulfate.

Citation Information

Cited By

  • Breathable warm-keeping quilt with composite structure and preparation method of breathable warm-keeping quilt

    CN121084033A